Policy Issues in the Clinical Development and Use of Immunotherapy for Cancer Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Immunotherapy is a form of cancer therapy that harnesses the body's immune system to destroy cancer cells. In recent years, immunotherapies have been developed for several cancers, including advanced melanoma, lung cancer, and kidney cancer. In some patients with metastatic cancers who have not responded well to other treatments, immunotherapy treatment has resulted in complete and durable responses. Given these promising findings, it is hoped that continued immunotherapy research and development will produce better cancer treatments that improve patient outcomes.
Keywords: Health and Medicine

Assessing Health Outcomes Among Veterans of Project SHAD (Shipboard Hazard and Defense) - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Between 1963 and 1969, the U.S. military carried out a series of tests, termed Project SHAD (Shipboard Hazard and Defense), to evaluate the vulnerabilities of U.S. Navy ships to chemical and biological warfare agents. These tests involved use of active chemical and biological agents, stimulants, tracers, and decontaminants. Approximately 5,900 military personnel, primarily from the Navy and Marine Corps, are reported to have been included in Project SHAD testing.
Keywords: Health and Medicine

Biomarker Tests for Molecularly Targeted Therapies: Key to Unlocking Precision Medicine - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Every patient is unique, and the evolving field of precision medicine aims to ensure the delivery of the right treatment to the right patient at the right time. In an era of rapid advances in biomedicine and enhanced understanding of the genetic basis of disease, health care providers increasingly have access to advanced technologies that may identify molecular variations specific to an individual patient, which subsequently can be targeted for treatment. Known as biomarker tests for molecularly targeted therapies, these complex tests have the potential to enable the selection of the most beneficial treatment (and also to identify treatments that may be harmful or ineffective) for the molecular underpinnings of an individual patient's disease. Such tests are key to unlocking the promise of precision medicine.
Keywords: Health and Medicine

Examining Access to Nutrition Care in Outpatient Cancer Centers: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
An estimated 90 percent of oncology patients in the United States receive treatment in outpatient cancer centers and clinics. This change from the older model of inpatient care has important implications for overall quality of care for oncology patients and nutritional care in particular. Amidst growing concern about access to oncology nutrition services, combined with growing recognition of the importance of providing nutritional care to optimize oncology treatment outcomes and maximize quality of life among both patients and survivors of cancer, the National Academies of Sciences, Engineering, and Medicine convened a public workshop in March 2016 to explore evolving interactions between nutritional care, cancer, and health outcomes.
Keywords: Food and Nutrition; Health and Medicine

Mitochondrial Replacement Techniques: Ethical, Social, and Policy Considerations - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Mitochondrial replacement techniques (MRTs) are designed to prevent the transmission of mitochondrial DNA (mtDNA) diseases from mother to child. While MRTs, if effective, could satisfy a desire of women seeking to have a genetically related child without the risk of passing on mtDNA disease, the technique raises significant ethical and social issues. It would create offspring who have genetic material from two women, something never sanctioned in humans, and would create mitochondrial changes that could be heritable (in female offspring), and therefore passed on in perpetuity. The manipulation would be performed on eggs or embryos, would affect every cell of the resulting individual, and once carried out this genetic manipulation is not reversible.
Keywords: Health and Medicine